2008
DOI: 10.1016/j.jconrel.2007.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound assisted siRNA delivery using PEG-siPlex loaded microbubbles

Abstract: Short interfering RNA (siRNA) attracts much attention for the treatment of various diseases. However, its delivery, especially via systemic routes, remains a challenge. Indeed, naked siRNAs are rapidly degraded, while complexed siRNAs massively aggregate in the blood or are captured by macrophages. Although this can be circumvented by PEGylation, we found that PEGylation had a strong negative effect on the gene silencing efficiency of siRNA-liposome complexes (siPlexes). Recently, ultrasound combined with micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
76
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 110 publications
(80 citation statements)
references
References 48 publications
3
76
1
Order By: Relevance
“…We showed that in combination with ultrasound, such microbubbles strongly improved both doxorubicin (DOX) cytotoxicity and pDNA [16,22] and siRNA [23] delivery to cells in vitro. However, the complex microbubble preparation method, the immunogenic nature of the avidin-biotin chemistry used to link the liposomes/lipoplexes to the microbubbles and the successive washing steps, made this material not ideal for easy clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…We showed that in combination with ultrasound, such microbubbles strongly improved both doxorubicin (DOX) cytotoxicity and pDNA [16,22] and siRNA [23] delivery to cells in vitro. However, the complex microbubble preparation method, the immunogenic nature of the avidin-biotin chemistry used to link the liposomes/lipoplexes to the microbubbles and the successive washing steps, made this material not ideal for easy clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…Among non-viral techniques, ultrasound-targeted microbubble destruction (UTMD) has evolved as a new, promising tool for site-specific drug and gene delivery in vitro and in vivo, targeting delivery via a process called sonoporation, allowing for direct transfer into the cells (14)(15)(16). Significant efforts have been made to demonstrate the application of siRNA mediated by UTMD to block gene expression in vitro and in vivo (17)(18)(19)(20). Wang et al (21) found that UTMD was capable of delivering survivin siRNA into SKOV-3 cells, which inhibited survivin expression and induced apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Without the need to use viral vectors, sonoporation enables the delivery of a wide range of bioactive agents with minimal inflammatory and immunological responses for both in vitro studies and in vivo applications (12)(13)(14)(15)(16). In addition, ultrasound application can be targeted to a specific volume of tissue in vivo noninvasively.…”
mentioning
confidence: 99%